Purification of Crocin-I from Gardenia Yellow by Macroporous Resin Columns In-Series and Its Antidepressant-Like Effect - Yu Jiang; Susu Lin; Qiaoqiao Li; Yingpeng Tong; Ping Wang (Journal of Chemistry)
In this study, the purification of crocin-I from Gardenia yellow by macroporous resin columns in-series was systematically investigated. The in-series macroporous adsorption resins consisting of XAD 4 and XAD 1600N resins were selected on the basis of the evaluation of performance and separation characteristics of 17 kinds of resins, including the adsorption capacities, desorption ratio, and separation degree. According to the analysis results, the optimum conditions were as follows: bed volume ratio of XAD 4 and XAD 1600N resins, sample volume, flow rate, and methanol concentration were 3 : 1, 5 BV, 15 BV/h, and 70%, respectively (BV was the bed volume of XAD 4 resin). After one run treatment, the separation degree of crocin-I at 254 nm and 440 nm decreased from 1.92 to 0.08 (DC−254 nm) and from 0.71 to 0.36 (DC−440 nm), respectively. The results showed that the in-series macroporous resins revealed a high capacity in the purification of crocin-I. Meanwhile, in the animal experiment, the forced swimming tests were regulated by crocin-I and Gardenia yellow, which demonstrated that crocin-I was the main constituent of Gardenia yellow and had potential antidepressant biological activities.